Implementation of the Prudent Principle in Murābaḥah Financing Operations at KSPPS Assyafi'iyah Metro Lampung Branch - Nur Halimah; Asyari Hasan (KURAS Institute, 2025)
Murābaḥah financing is financing carried out for the ownership of certain goods that are paid at maturity. This study aims to determine the implementation of the prudent principle in the operation of murābaḥah financing at KSPPS BMT Assyafi'iyah Metro Lampung Branch. This study uses a qualitative approach with a case/field study. The case study approach was chosen because it allows researchers to explore in depth the process of implementing the principle of prudence in the operational context of murābaḥah financing. The results of this study state that murābaḥah financing at KSPPS BMT Assyafi'iyah applies the principle of prudence (prudent principle) which aims to avoid problematic customers and minimize the risk of loss for the BMT. The principle of prudence (prudent principle) applied by KSPPS BMT Assyafi'iyah is the 5C + S aspect (character, capital, capacity, collateral, condition of economic and sharia).